Enhancing Scientific Communication through its Latitudes and the Fundamental Factors of Virtue - Mendoza Villalobos, Yesenia (2019)
Virtue is a subject addressed from different perspectives, with inclusions, exclusions and repetitions of characteristics that give or nullify meaning to its essence. This article identifies the pillars that support the existence of the same, analyzing and contrasting different aspects found in the cited literature. Three factors are proposed: moral fact, character and will, which are raised and justified as elementary and necessary to prevail as such. In turn, based on these elements of virtue, three latitudes were detected: knowledge and reason; actions done; and intentionality. The parallelism between these factors of virtue and latitudes of scientific communication can be expressed in the following ways: (i) the character factor corresponds to the latitude of knowledge and reason since the knowledge of the researcher's science would include handling of literature , tools, techniques and methods; (ii) the moral fact as an element of virtue, gives rise to the latitude of actions carried out in scientific culture, including the investigative act itself, the fieldwork, the writing of articles, and the search for spaces for communication; and (iii) the element of the will, which brings with it the latitude of intentionality, implies the inclination and interest of the researcher, whether motivated by his search for recognition, personal or professional achievement and enables the achievement of incentives to continue carrying out the scientific activity.